Rainfall and PM Removal on Tree Leaves: A Study of Santiago, Chile’s Native Species - Margarita Préndez; Karina Corada; Ignacio Navarrete; Javier Vera; Zilera Wyss (Atmosphere)
Green infrastructure, such as street trees, can help improve air quality, but the role of rainfall in cleaning total particulate matter (TPM) from tree leaves is not well understood, especially in cities like Santiago, Chile. This study measured TPM deposited on leaves and its elemental composition of two native tree species, Quillaja saponaria and Schinus molle, by five independent rainfall episodes. The results showed significant differences in how each tree species responded to rainfall. The total amount of TPM finally removed or retained at the leaf level in the five rainfall events studied was 4.72 and 8.43 mg/gldw for Q. saponaria and S. molle, respectively. Q. saponaria decreased TPM levels after rainfall, while S. molle exhibited mixed responses, increasing or decreasing TPM accumulation on leaves after different intensities of rainfalls. Elemental analysis revealed metals such as lithium and nickel—potentially linked to electric vehicle batteries—and tin and antimony–potentially linked to industrial processes. Rainfall benefited air quality by removing heavy metals from the atmosphere and aiding plant recovery from TPM accumulation. However, further research is needed on metal speciation in TPM and its foliar uptake by plants. This study provides some insights into the complex interactions between trees leaves, TPM deposition, and rainfall.